Syncing to perform? A naturalistic uncontrolled prospective case study of emotional and physiological synchrony in a team of male volleyball athletes - Tamminen, K. A.; Danyluck, C.; Bonk, D.; Chen, R. (Journal of Sports Sciences, 2023)
Group processes are important for promoting relational and performance-related outcomes in sport; however, research exploring emotional and physiological synchrony and performance outcomes is rare. The objective of this study was to examine perceived emotional synchrony, physiological synchrony, and performance among male volleyball players using a naturalistic uncontrolled prospective case study approach over nine practices. Athletes participated in a coach-led pre-practice group visualization routine, while their heart rate and heart rate variability were continuously monitored. Athletes completed post-practice measures of emotional synchrony, and athletes and coaches completed ratings of individual and team performance. Emotional and physiological synchrony were not significantly correlated, but they were differentially related to performance outcomes, and there were significant interaction effects between physiological synchrony and time. Athletes` ratings of their own and their team`s performance were associated with their perceived emotional synchrony. Coach performance ratings were associated with pre-practice team physiological synchrony but were unrelated to athletes` perceived emotional synchrony. Heart rate synchrony was associated with athlete and coach performance ratings and may be important for team dynamics and performance outcomes. The findings demonstrate evidence for emotional and physiological synchrony among athletes, providing a platform for future research examining processes and impacts of synchrony in sport.